2008
DOI: 10.1080/02688690801969489
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus complicating a cervical spine fracture in a patient with ankylosing spondylitis

Abstract: We present a case of obstructive hydrocephalus secondary to ascending spinal cord oedema, sustained after cervical spine fracture in a patient with ankylosing spondylitis. To our knowledge, this is the first report of ascending oedema from a cervical cord injury causing obstructive hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Spreading of spinal cord edema as high as the medulla oblongata after a cervical SCI has also been reported10). Challagundla et al1) reported on a case of hydrocephalus following fracture dislocation of C5-6 in a patient with ankylosing spondylitis. He postulated that hydrocephalus resulted from obstruction of CSF flow at the fourth ventricular outlets due to ascending edema of the medulla oblongata from the cervical spine.…”
Section: Discussionmentioning
confidence: 88%
“…Spreading of spinal cord edema as high as the medulla oblongata after a cervical SCI has also been reported10). Challagundla et al1) reported on a case of hydrocephalus following fracture dislocation of C5-6 in a patient with ankylosing spondylitis. He postulated that hydrocephalus resulted from obstruction of CSF flow at the fourth ventricular outlets due to ascending edema of the medulla oblongata from the cervical spine.…”
Section: Discussionmentioning
confidence: 88%
“…Yablon et al10) suggested that the swelling of the spinal cord, observed after spinal trauma, may extend up to two vertebral segments above and below the injured vertebrae. Challagundla et al1) reported a case of hydrocephalus following fracture dislocation of C5-6 in a patient with ankylosing spondylitis. He postulated that hydrocephalus resulted from the obstruction of CSF flow at the fourth ventricular outlets due to the ascending edema of the medulla oblongata from the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…A whole-body CT scan performed upon admission of the patient revealed a Type II dens axis fracture4 and serial rib fractures. No other injuries of the head, spine or torso were found.…”
Section: Investigationsmentioning
confidence: 99%
“…Cerebrospinal fluid (CSF) leaks after spine surgery are well documented and are among the most commonly reported complications, occurring in approximately 15% of patients undergoing spine surgery 3. Usually, postoperative leakage of CSF leads to subcutaneous fluid accumulation at the operation site, but has no obstructive effect on liquor circulation, whereas the development of a hydrocephalus after cervical spine fractures, especially in association with pre-existing malformations, malignancies or inflammations, as a complication is known 4. The development of a hydrocephalus communicans (a combined form of hydrocephalus occlusivus and hydrocephalus maleresorbtivus ) after fractures of the upper cervical spine in healthy older patients5 has never been reported to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%